PENGARUH SKEPTISME PROFESIONAL, INDEPENDENSI, KOMPETENSI DAN ETIKA AUDITOR TERHADAP KEMAMPUAN AUDITOR DALAM PENDETEKSIAN KECURANGAN - Rinny Meidiyustiani; Nur Fitri Septiani (EKBIS (Ekonomi & Bisnis), 2020)
This study aims identify any influence of professional sceptism, independence, competence, and etics an auditors against the ability of Auditors to detect at the public accountant tangerang and south tangerang. The research method used is multiple regression linear analysis with the quantative approach. The data used in this research was the primary data. Data collection techniques likert scale using a questionnaire. Total 50 employees sampe in research who worked at the public accountant tangerang and south tangeran, with the sample use sampling techniques convenience or accidental sampling. The data from the questionnaires process in statistics using spp 20 version. As much as 99,1 % ability in the detection of fraud can be explained by variable professional skepticism, independence, competence and etics an auditors. The result of this research suggest the profesional skepticism, independence and ethics an auditors significant impact on the ability of the auditors in fraud detection